Model Regresi Nonparametrik Deret Fourier pada Pola Data Curah Hujan di Kota Mataram - Widiya Tri Astuti; Mustika Hadijati; Irwansyah - (Eigen Mathematics Journal, 2018)
Rainfall is one of the elements of the climate that has influence on people's lives in West Nusa Tenggara Province. Thecapital city of West Nusa Tenggara Province (NTB), namely the City of Mataram, in December 2016 was affected byflood disaster due the rainfall increation. This causes all activities in the City of Mataram paralyzed. This study aimed tomodelling the rainfall and to determine the rainfall grade prediction in the City of Mataram in 2017. The method usedwas nonparametric regression of Fourier series. Based on the results of the analysis that has been committed, the bestFourier series of nonparametric regression model obtained at the Selaparang station was a model with 101 number ofknots and 0.959116 value of R2 . For the Ampenan station, the best model obtained with 101 knots and 0.966992 valueof R2 . As well as for the Cakranegara station, the best model obtained with 106 number of knots and 0.987778 value ofR2 .